2021
DOI: 10.3390/jcm10081599
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia and Intracranial Venous Sinus Thrombosis after “COVID-19 Vaccine AstraZeneca” Exposure

Abstract: Background: As of 8 April 2021, a total of 2.9 million people have died with or from the coronavirus infection causing COVID-19 (Corona Virus Disease 2019). On 29 January 2021, the European Medicines Agency (EMA) approved a COVID-19 vaccine developed by Oxford University and AstraZeneca (AZD1222, ChAdOx1 nCoV-19, COVID-19 vaccine AstraZeneca, Vaxzevria, Covishield). While the vaccine prevents severe course of and death from COVID-19, the observation of pulmonary, abdominal, and intracranial venous thromboembol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(173 citation statements)
references
References 31 publications
6
154
1
5
Order By: Relevance
“…Finally, several international reports have been published highlighting the possibility of thrombohemorrhagic complications within the time interval of 5 to 16 days after the first dose of the adenoviral vector vaccine ChAdOx1-19 against COVID-19 [7][8][9]18]: these data confirmed that the analyzed cases may be definitively classified as AEFI caused by vaccination.…”
Section: Ihc Findings (Figure 3)mentioning
confidence: 53%
See 3 more Smart Citations
“…Finally, several international reports have been published highlighting the possibility of thrombohemorrhagic complications within the time interval of 5 to 16 days after the first dose of the adenoviral vector vaccine ChAdOx1-19 against COVID-19 [7][8][9]18]: these data confirmed that the analyzed cases may be definitively classified as AEFI caused by vaccination.…”
Section: Ihc Findings (Figure 3)mentioning
confidence: 53%
“…Moreover, in order to develop specific evidence-based items, an exhaustive review of the pertinent literature was performed. To date, several reports have been published reporting severe adverse effects (thrombosis and thrombocytopenia) after COVID-19 vaccination [7][8][9][16][17][18][19]. Each report was analyzed independently by each author of this article in order to identify specific items.…”
Section: Vaccine Characteristics and Exhaustive Review Of The Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The ChAdOx1-nCoV 19 is another adenovirus-based vaccine for which data on VITT have been published in the medical literature. There are data on 58 cases(45 females) of whom 48 were aged <60 [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ]. The twin derangements of thrombocytopenia and raised D-dimer levels were documented in 51 cases.…”
mentioning
confidence: 99%